The effect of the organizational commitment on the organizational agility in the Directorate of Education at Qalqilya District - Alaqra, Obayda Abd-Elhadi Abd-Elqader (Journal of Economic, Administrative and Legal Sciences, 2022)
The study aimed to identify the effect of the organizational commitment on the organizational agility in the Directorate of Education at Qalqilya District, and the effect of the organizational commitment on the agility of sensing and decision-making in the Directorate of Education at Qalqilya District. Furthermore, to know if there is a related relationship between the organizational commitment and the organizational agility in the Directorate of Education at Qalqilya District. In addition, to find out if there is a role for the demographic variables (gender, academic qualification, years of experience, and the job title), the researchers achieved the study objectives by utilizing the descriptive analytical approach, using a questionnaire that consists of (31) paragraphs. It was distributed to a representative sample of the study community, which was made up of all the employees (66) of the Directorate of Education at Qalqilya District, they were randomly selected. The results of the study confirmed that there was amoderate related relationship between the effects of the organizational commitment on the organizational agility and the individual responses of the study sample towards the effect of the organizational commitment on the organizational agility in the Directorate of Education at Qalqilya Governorate were high in (1 and 3) domains, related to the sensing agility and the relationship between the organizational commitment and the organizational agility with Percentage between (70%-79%). Additionally, it was moderate in the (2) domain related to decision-making agility with Percentage between (60%-69%), The researcher recommended the importance of training the higher management in the directorate to suit the needs of employees through specialized courses, and implementing some training programs that increase the levels of their organizational commitment and the organizational agility. Moreover, and enriching the higher management in the directorate, bases the work and the dynamics of decision-making. Also, the use of the available information in making efficient decisions, the researchers recommended also working on distributing a guide for participatory work and the agility in decision-making.
Keywords: organizational commitment; organizational agility; Directorate of Education; Qalqilya District